The influence of different sources of anticipated instrumental support on depressive symptoms in older adults - Fu, Duanduan; Wang, Fang; Gao, Baizhi; Bai, Qin; Liu, Guilin; Zhu, Jinghui (Frontiers in Public Health, 2024)
Objective This study investigated how anticipated instrumental support sources and intergenerational support influence depressive symptoms in older Chinese adults. Methods We employed binary logistic regression on data from 7,117 adults aged ≥60 in the 2018 China Health and Retirement Longitudinal Study, controlling for gender, marital status, and self-rated health. Results 38.89% of respondents exhibited depressive symptoms. Anticipated support from spouse and children, spouse only, children only, or other sources showed 52, 25, 46, and 40% lower odds of depression, respectively, compared with no anticipated support. Those providing financial support had 36% higher odds of depression than those without exchanges. However, those receiving financial support, receiving instrumental support, and receiving and providing financial and emotional support had 19, 14, 23, and 24% lower odds of depression. Conclusion Different anticipated instrumental support sources and intergenerational support influenced depression odds in older adults, suggesting potential benefits in promoting such support systems.